2022
DOI: 10.1007/s40264-022-01194-z
|View full text |Cite
|
Sign up to set email alerts
|

Post-Marketing Surveillance of CAR-T-Cell Therapies: Analysis of the FDA Adverse Event Reporting System (FAERS) Database

Abstract: Introduction As chimeric antigen receptor T-cell therapies are becoming increasingly available in the armamentarium of the hematologist, there is an emerging need to monitor post-marketing safety. Objective We aimed to better characterize their safety profile by focusing on cytokine release syndrome and identifying emerging signals. MethodsWe queried the US Food and Drug Administration Adverse Event Reporting System (October 2017-September 2020) to analyze suspected adverse drug reactions to tisagenlecleucel (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 37 publications
2
19
1
Order By: Relevance
“…According to the FDA Adverse Event Reporting System for tisagenlecleucel in the post-marketing period for the pediatric population, infection was the second most frequent cause of death (11.3%) after disease progression [ 172 ]. Another post-marketing surveillance study of tisagenlecleucel in adults and children revealed a relatively small number of children undergoing CAR T-cell therapy (<0.5%) and higher fungal infection rates (5.4%) [ 173 ]. Not surprisingly, treatment of r/r ALL pediatric patients with other types of CD19-specific CAR T-cells documented comparable with tisagenlecleucel grade ≥3 infection rates (21–24%) [ 159 , 174 ].…”
Section: Chimeric Antigen Receptor T-cells (Car T-cells)mentioning
confidence: 99%
“…According to the FDA Adverse Event Reporting System for tisagenlecleucel in the post-marketing period for the pediatric population, infection was the second most frequent cause of death (11.3%) after disease progression [ 172 ]. Another post-marketing surveillance study of tisagenlecleucel in adults and children revealed a relatively small number of children undergoing CAR T-cell therapy (<0.5%) and higher fungal infection rates (5.4%) [ 173 ]. Not surprisingly, treatment of r/r ALL pediatric patients with other types of CD19-specific CAR T-cells documented comparable with tisagenlecleucel grade ≥3 infection rates (21–24%) [ 159 , 174 ].…”
Section: Chimeric Antigen Receptor T-cells (Car T-cells)mentioning
confidence: 99%
“…Recognition, management, and differentiation of CAR-T cell toxicities are crucial for safe and broad employment of this therapy. Real world data confirmed the well-known adverse reactions of CAR-T cells and in some analyses lower severe CRS and ICANS rates were reported most likely due to the fact that clinical experience improved their early detection [6][7][8][9]. Furthermore, use of corticosteroids to mitigate toxicities by inhibiting the proliferation and/or inflammatory cytokine production from CAR-T cells and other immune cells has become more liberal with initiation at lower grades of CRS or ICANS [6,7].…”
mentioning
confidence: 63%
“…
CD19-targeted chimeric antigen receptor-engineered (CAR)-T cells are novel therapies showing great promise for patients with relapsed or refractory diffuse large B cell lymphoma (DLBCL), primary mediastinal B cell lymphoma, mantle cell lymphoma, and follicular lymphoma. EMA-approved and commercially available CAR-T cell products have been used successfully by qualified CAR-T cell centers worldwide and these real world data compare favorably to pivotal study results with overall response rates (ORR) and complete response rates (CR) ranging from 51-93% and 40-64%, respectively [1][2][3][4][5][6][7][8][9].Recently, axicabtagene ciloleucel (axi-cel) received FDA approval based on results of a multicenter, randomized study comparing axi-cel to conventional salvage chemoimmunotherapy and autologous blood stem cell transplantation (ASCT) as second-line treatment in patients with relapsed or refractory DLBCL [10,11]. After a median follow-up of 24.9 months, median event-free survival (EFS) was more than 4-fold greater and ORR was 33% higher with double the CR rate in the axi-cel arm.
…”
mentioning
confidence: 89%
See 2 more Smart Citations